Determine tg [pi/2 - arctg(1/2)] .

Expert Answers
hala718 eNotes educator| Certified Educator

tg(pi/2 -arctg(1/2)

We know that :

ctg (x)= tg(pi/2 - x)

==> tg(pi/2 -arctg(1/2)= ctg (arctg(1/2)

                               = ctg(arc ctg (2)

                              = 2

neela | Student

To detrmine  tg {pi/2 - arctg (1/2)}

Solution:

We know that tan (pi-x) = 1/tanx

So tan {pi/2-arctan (1/2)} = 1/ tan {arc tan(1/2)}

= 1/tan (1/2)

= 1/tan (0.5radians)

= 1/tan (28.64789 deg)

= 1.83049 nearly

giorgiana1976 | Student

We'll use the formula tg(pi/2 - k) = ctg k.

Now, we'll apply the formula, where k = arctg(1/2)

tg[pi/2 - arctg(1/2)] = ctg [arctg(1/2)]

But ctg k = 1/tg k

ctg [arctg(1/2)]=1/tg(arctg(1/2))=1/(1/2)=2

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question